Measurement of perceived barriers to physical activities: Proposed research instrument - Edio Luiz Petroski; Marcelle de Oliveira Martins (Universidade Federal de Santa Catarina, 2000)
Currently, one of the most-investigated subjects that Physical Education scientists are researching consists of themes related to human behavior (change of patterns, habits related to the health, lifestyle, beliefs and attitudes, motivation for physical activity, perception of barriers). The aim of the present article is to propose an objective instrument (questionnaire) to be used in research into human behavior, especially related to the perception of barriers to the practice of physical activity. The study used a sample of 42 adults (22 women and 20 men) and had the following methodological design: preliminary test-retest with one week interval, reformulation of the instrument, final test-retest with one week interval. The reliability of the proposed barriers was initially evaluated using the Kappa index and Pearson Product Moment correlations. Testing of the instrument demonstrated that the proposed questionnaire (a list of nineteen barriers evaluated in ordinal scale) can be easily employed, due to its applicability and quite satisfactory clarity, in addition to offering a reproducibility index of adequate reliability. RESUMO Atualmente, temas relacionados a comportamento (mudança de padrões, hábitos relacionados à saúde, estilo de vida, crenças e atitudes, motivação para a prática, percepção de barreiras) estão entre os assuntos mais investigados pelos cientistas da área da Educação Física. O presente trabalho tem o intuito de propor um instrumento (questionário) objetivo a ser utilizado em pesquisas sobre comportamento humano, especialmente relacionado à percepção de barreiras para a prática de atividades físicas. Participaram do estudo 42 indivíduos adultos (22 mulheres e 20 homens), com o seguinte design metodológico: teste-reteste preliminar com intervalo de uma semana, reformulação do instrumento, teste-reteste final, com intervalo de uma semana. A reprodutibilidade das barreiras propostas foi avaliada inicialmente através do cálculo do índice Kappa, e posteriormente comparou-se os resultados de pré e pós teste (escore total e quantidade de barreiras) através do teste de correlação de Pearson. A testagem do instrumento demonstrou que o questionário proposto (uma lista de dezenove barreiras avaliadas em escala ordinal) pode ser facilmente utilizado, devido à aplicabilidade e clareza bastante satisfatórias, além de permitir um índice de reprodutibilidade de respostas adequado.